Efektivitas Promosi Kesehatan Berbasis Media Digital Dalam Meningkatkan Pengetahuan Kesehatan Masyarakat - Sunia Mawarni Laia (Jurnal Ilmu Kesehatan Terpadu Indonesia, 2026)
Health promotion is an important strategy for improving public knowledge and awareness of various health issues. The rapid development of information and communication technology has encouraged the use of digital media as a broader, faster, and more interactive approach to health promotion compared to conventional methods. Various digital platforms, including social media, mobile health applications, health websites, educational videos, webinars, and podcasts, have been utilized to disseminate health information to the public. This study aimed to examine the effectiveness of digital media-based health promotion in improving public health knowledge through a literature review approach. Literature was searched through Google Scholar, PubMed, ScienceDirect, SpringerLink, and Garuda databases using keywords related to digital health promotion and health knowledge. The reviewed articles were published between 2016 and 2026 and met the predetermined inclusion and exclusion criteria. The findings indicate that digital media-based health promotion is effective in improving public health knowledge across various health topics, including disease prevention, reproductive health, nutrition, mental health, and healthy lifestyle behaviors. The effectiveness of digital media is supported by easy access to information, wide coverage, attractive content presentation, and interactive communication features. However, its effectiveness is influenced by the level of digital literacy, the quality of health information provided, and access to technology. Therefore, digital media-based health promotion can be considered an effective strategy for enhancing public health knowledge and supporting the development of innovative health programs in the digital era.